2020
DOI: 10.18176/jiaci.0439
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Allergen Profiling of Dual Mite Sensitization in Severe Allergic Rhinitis

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…Mono-sensitization to Der p 23 was as low as 3% and also comparable to Weghofer et al [12] showing that 4% of patients were mono-sensitized to Der p 23. Also, González-Pérez et al [13] reported a mono-sensitization of 3% towards Der p 23 in Spain. Although mono-sensitization seems to be a rare event, Matos Semedo et al [24] argue that Der p 23 itself has clinical relevance and should probably be considered in terms of HDM-specific immunotherapy extract composition.…”
Section: Discussion/conclusionmentioning
confidence: 97%
See 2 more Smart Citations
“…Mono-sensitization to Der p 23 was as low as 3% and also comparable to Weghofer et al [12] showing that 4% of patients were mono-sensitized to Der p 23. Also, González-Pérez et al [13] reported a mono-sensitization of 3% towards Der p 23 in Spain. Although mono-sensitization seems to be a rare event, Matos Semedo et al [24] argue that Der p 23 itself has clinical relevance and should probably be considered in terms of HDM-specific immunotherapy extract composition.…”
Section: Discussion/conclusionmentioning
confidence: 97%
“…The aim of the study was to investigate the prevalence of IgE reactivity to Der p 23 in a relatively large sample of patients in southern Bavaria based on the evidence that Der p 23 could be a major allergen of HDM, as already published for other regions [9,10,[12][13][14][15]. According to the result patients were separated in patients with allergic symptoms to house dust mite (n = 67) and patients with clinically silent sensitization (n = 50) (a as ratio with total serum IgE, p = 8.867, b as ratio with sIgE to D.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, lots of studies have been focused on common allergens testing in the specific populations [6][7][8]. There are different allergen sensitizaton patterns in various regions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high prevalence of sIgE response to Der p 23, only 2 subjects (2.17%) were exclusively sensitized to Der p 23 in our sample. The high prevalence (>85%) of Der p 23 sIgE confirmed the importance of this allergen component as a major HDM allergen supported by former research from Austria [41], Thailand [42], and Spain [43]. Batard et al [44] equally reported that in temperate regions, 20–47% of 1,302 HDM allergic patients also showed sIgE to allergens from groups 4, 5, 7, 13, 15, 21, and 23.…”
Section: Discussionmentioning
confidence: 67%